The use of intelligent automation as a form of digital transformation in tourism: Towards a hybrid experiential offering - Christou, Prokopis A.; Hadjielias, Elias; Simillidou, Aspasia; Kvasova, Olga (My University, 2023)
The purpose of this study is to explore the extent to which intelligent automation (IA) should be used to provide the best possible service quality and experience to customers, an area that needs further exploration. The study draws on an inductive qualitative inquiry from the supply side which has been rather overlooked despite its significant role in designing and shaping experiences. The data were gathered by conducting a total of 39 semi-structured interviews with tourism service providers in Cyprus. The findings revealed insightful information regarding human-IA tasks and interaction from a tourism provider perspective while stressing the cooperation between humans and IA within a service context. The importance of the human element, individual characteristics and key human capabilities are particularly stressed within a continuous digitally transformative industry. The paper concludes with theoretical contributions in regard to the experiential theoretical milieu, practical implications, and future research directions.
Keywords: Customer service; Digital transformation; Intelligent automation; Qualitative research; Tourism; Tourist experience